Challenges of sexually transmitted infections and HIV/AIDS prevention and control programme in Malaysia: a scoping review - Selly Jaimon; Khalid Mokti (Malaysian Public Health Physicians Association, 2024)
Sexually Transmitted Infections (STIs) encompass a range of bacterial, viral, and parasite illnesses that can be transferred via sexual activity, including oral-genital contact and the sharing of certain objects or substances. HIV is a pathogenic infection that targets and compromises the functioning of the body's immune systems while AIDS represents the most advanced phase of the disease. The Western Pacific region exhibits the highest rates of incidence and prevalence of treatable STIs globally. While HIV prevalence in the region remains low at 0.1%, an estimated 100,000 new HIV infections continue to occur annually particularly among key populations. Malaysia reported a cumulative number of reported HIV and AIDS at 125,878 and 28,805 respectively in 2020. Unfortunately, Malaysia is off tracked of its 2020 objectives of reaching 95-95-95 targets in the testing-treatment-viral suppression cycle. While, sexual intercourse is the primary means through which both HIV and other STIs are transmitted. The preventive measures aimed at reducing the sexual transmission of HIV and STIs are similar, as are the target populations for intervention strategies. Hence, the identification of issues or constraints in STIs prevention and control programmes constitute a crucial component of HIV/AIDS prevention and control approach. This is a scoping review on sexually transmissible infections and HIV/AIDS prevention and control programs in Malaysia to determine the issues and constraints and also to analyse the challenges in implementing effective prevention programmes in Malaysia. Three online databases were used to identify articles published from 2014-2023, primary study from any type of study design conducted in Malaysia and studies with STI and HIV/AIDS as primary or secondary outcome. NonEnglish articles and those that were unable to have full access are excluded. A total of 16122 studies were screened against the eligibility criteria and 12 studies were included in the review. Majority of the included studies were conducted in East Malaysia and 77% of the articles reported quantitative study design. Generally, the studies examined STIs and HIV/AIDS challenges were among the key populations (41.7%). Highlighted challenges on prevention and control programmes were on knowledge, followed by issues of testing, stigma, issues on privacy and confidentiality, healthcare worker's challenges perspectives, and on barriers of implementation of pre-exposure prophylaxis. As conclusion, most studies focused on key populations, done in the states of West Malaysia and mainly are on HIV/AIDS rather than STIs. Barriers of poor knowledge and stigma remained the prevalent issues in Malaysia, and this review was unable to identified any study on pre-exposure prophylaxis as prevention and control strategy as it is still in the engagement session. The result of this review underscores the need for more rigorous study and improved quality of reporting of STIs and HIV/AIDS in order to support public health decision-making in Malaysia.